STATUS SOSIAL “MISKIN” PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN BERDASARKAN TEORI DRAMATURGI ERVING GOFFMAN DI COT GUD SEUNAGAN TIMUR - Rika Sasnita; Yeni Sri Lestari (Jurnal Society : Pengamat Perubahan Sosial, 2022)
Since 2007, the Indonesian government has adopted the Family Hope Program to accelerate poverty reduction and created a social security program (PKH). A conditional social assistance program known as the Family Hope Program (PKH) is available for low-income families identified as PKH beneficiary families (KPM). The Family Hope Program (PKH) aims to reduce the current level of poverty more than anything else. It also aims to create a social security system for the poor. This study aims to determine the social behavior of beneficiaries of the family hope program based on erving goffman’s dramatugi theory in Gampong Cot Gud, East Seunagan Timur, in this study using qualitative methods with informant withdrawal techniques prioritizing the quality of data obtained thourgh the submission of informants related to research problems, data collection techniques namely in-depth intreviews and documentation.